Co-benefits of subnationally differentiated carbon pricing policies in China: Alleviation of heavy PM2.5 pollution and improvement in environmental equity. (February 2021) - Zhang, Wen-Wen; Zhao, Bin; Ding, Dian; Sharp, Basil; Gu, Yu; Xu, Shi-Chun; Xing, Jia; Wang, Shu-Xiao; Liou, Kuo-Nan; Rao, Lan-Lan
Abstract: Carbon policies differentiated according to regional disparities have been recognized and recommended. However, the air quality co-benefits of differentiated policies remain unclear. Here we combine a multi-regional dynamic computable general equilibrium (CGE) model and an extend response surface model (ERSM) to investigate the impact of nationally uniform and subnationally differentiated carbon pricing policies on fine particulate matter (PM2.5 ) concentrations in China. All policies examined lead to the same accumulated national CO2 emissions (2020–2050), with the 2030 emissions attaining China's national abatement target. We find that, when subnational policies differentiated according to provincial PM2.5 concentrations are implemented, the higher-than-average carbon price over more polluted provinces results in twice as much reduction in CO2 and air pollutant emissions in 2050 as the national policy. As a result, the subnational policies cause larger PM2.5 concentration reductions in these provinces (9%–18%) than the national policy (7%–11%). Also, the subnational policies eliminate high PM2.5 exposure of over 45 μg/m 3 which 12% people suffer from under the national policy. The subnational policies substantially reduce regional disparity in PM2.5 pollution and hence improve environmental equity. The results suggest that subnationally differentiated carbon policies are a promising instrument to mitigate severe pollution and promote environmental equity. Highlights: We evaluate air quality co-benefits of regional differentiated carbon policies. We construct a multi-regional dynamic CGE model and an ERSM model. The differentiated policy alleviates heavy PM2.5 pollution relative to a national one. The differentiated policy helps to promote environmental equity in China.